Hubungan Antara Dukungan Sosial Dengan Strategi Koping Klien Epilepsi Dewasa - Sujono, Sujono; Rahmat, Ibrahim; Akhmadi, Akhmadi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file